Modeling and Characteristic Analysis of Wireless Ultrasonic Vibration Energy Transmission Channels through Planar and Curved Metal Barriers - DingXin Yang; BaoJian Hou; Dong Tian; Siyuan Wang (Shock and Vibration)
Wireless ultrasonic vibration energy transmission systems through metal barriers based on piezoelectric transducers have drawn a lot of focus due to the advantage of nonpenetration of the barriers, thus maintaining the integrity of sealed structures. It is meaningful to investigate appropriate modeling methods and to characterize such wireless ultrasonic energy transmission channels with different geometric shapes. In this paper, equivalent circuit modeling and finite element modeling methods are applied to the planar metal barrier channel, and a 3-dimensional finite element modeling method is applied to the cylindrical metallic barrier channel. Meanwhile, the experimental setup is established and measurements are carried out to validate the effectiveness of the corresponding modeling methods. The results show that Leach’s equivalent circuit modeling method and finite element modeling method are nearly similarly effective in characterizing the planar metal barrier channel. But for a cylindrical metal barrier, only the three-dimensional finite element modeling method is effective. Furthermore, we found that, for the planar barrier, the effect of standing waves on the efficiency of wireless energy transmission is dominated. But for the curved barrier, only the resonant phenomenon of the piezoelectric transducer exists.